Efeito da imersão periódica em soluções limpadoras na rugosidade superficial, porcentagem de variação de massa e resistência flexural de ligas de cobalto-cromo - Borsa, Pedro Carlos Cortiana (2014)
The aim of this study was to evaluate the flexural strength, elastic modulus, mass changes and surface roughness of two cobalt-chromium alloys, before and after immersions in four cleaning solutions and distilled water (as control). Co-Cr alloys (Co-Cr®, Dentsply-DeguDent Industria e Comércio, São Paulo, Brasil; and GM 800+®, Dentaurum GmbH & Co KG, Ispringen, Alemanha) were investigated. Fifty bar specimens (25 x 3 x 0,5 mm) for the flexural test, 50 quadrangular specimens (10 x 10 x 1 mm) for mass changes evaluation and 35 cylindrical specimens (10 x 1 mm) for surface roughness measurements were obtained by casting. They were polished by abrasive paper (#240 to #2500) and diamond polishing paste (3μm). Specimens were randomly divided into 5 groups according the following cleaning, solutions: pure white vinegar, 0.2% peracetic acid, sodium perborate - Corega Tabs®, 0.37% sodium hypochlorite and the control, distilled water. Surface roughness (Ra parameter) was analyzed using a profilometer (Mitutoyo SJ 410, Mitutoyo Corp, Kanagawa, Japan) before and after 5, 20 e 90 immersions (10 min each). Ra changes (ΔRa5, ΔRa20 e ΔRa90) were calculated for the different intervals. Qualitative surface analyses were performed by Scanning Electron Microscope (JSM 6360 SEM, JEOL). Both alloys, immersed in pure white vinegar, 0.2% peracetic acid, sodium perborate - Corega Tabs®, 0.37% sodium hypochlorite had similar roughness changes after 90 immersions (ΔRa from -0,012 to 0,022 μm). There was a significant surface roughening in hypochlorite (ΔRa90= 0,064 μm for CoCr®; and ΔRa90 = 0,592 μm for GM 800+). The number of immersions influenced on the roughness changes only in hypochlorite and there were greater changes in the GM 800+ alloy. After 90 immersions, GM 800+ alloy showed mass lost in the hypochlorite solution (-0,3%). This alloy presented higher flexural strength after 90 immersions in SH (σF= 1516 MPa in hypochlorite; 1366 MPa in control). However, there were no elastic modulus changes. CoCr® alloy did not present differences in the σF or in elastic modulus in any solution. The only solution that damaged the alloy surface was 0.37% sodium hypochlorite.